Social networks and the construction of membership identities - (:unkn) unknown (My University, 2025)
In this research we intend to analyse the social networks of different types of migrants in order to better understand the construction of membership (or non-membership) criteria for different social, cultural and geographic categories. We propose an empirical analysis of migrant social networks and the construction of social membership. More generally, the study highlights the fundamental question of the importance and role of social relations in the context of migration research. In this sense, the study will participate centrally in the debate on ethnicity and on mechanisms of social exclusion and inclusion. Our main research question can be summarized as follows: what are the social networks of different types of migrants composed of, how are they structured and on the basis of what criteria are cultural and social membership categories constituted? In other terms, how can we best describe the conjunction between the forms of social networks and membership identities ? Our principal hypotheses is as follows: Socio-economic and legal factors, as well as educational variables, will have a considerable effect on the composition and forms of social networks, and will determine membership criteria. These factors are more important than "ethnic" or "national" origin and "culture". In order to answer these questions, we have chosen a research design following two stages. In our first stage, we will record the personal social networks of 300 habitants of Neuchâtel, migrants as well as non-migrants. From an methodological point of view, the study adopts the perspective of classical "network analysis", as it is practiced in social anthropology and sociology. In order to be able to interpret the standardized network data and to attain a more in-depth comprehension of the topic, in a second stage we will conduct 10-20 case studies. Participant observation, narrative, semi-structured interviews, and in-depth-interviews with reference persons, etc. are some of the methods which will be applied in this stage. The research will be carried out in Neuchâtel.
Keywords: social networks; boundary work; transnationalism